MERAWAT KEMAJEMUKAN BANGSA DENGAN IMAN DAN TAQWA - Muhith Muhmmad Ishaq (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2023)
This research aims to understand what it is like to care for national diversity through an approach of faith and piety. The research method used is qualitative with literature study. All primary and secondary research data comes from the library, namely the Al-Qur'an, tafsir books, hadith, journals and research published online. The data analysis methods used are data reduction, data display, and drawing conclusions. The nature of the data analysis used is descriptive analytical. The conclusion of this research is that the threat of disintegration is inevitable for every union, including national and state ties. Efforts to maintain and maintain the integration of Indonesian nationality which have been emphasized since the Youth Pledge in 1928 are an obligation for every Indonesian citizen. The Muslims who are the majority population of this country have a very large role and contribution to maintaining the integrity of the nation from the threat of disintegration. The Indonesian state which is based on Pancasila requires its citizens to be religious, uphold human values, maintain unity, deliberate with wisdom and wisdom, and realize social justice for all its people. Taqwa is one of the fruits of all ummah worship and is a great energy for maintaining unity and unity. Devotion to Allah subhanahu wa ta'ala fosters a sense of brotherhood between people. And this brotherhood that is built on the foundation of faith and piety is what will maintain the survival and continuity of that brotherhood even in the afterlife.